2021
DOI: 10.1152/ajpgi.00059.2021
|View full text |Cite
|
Sign up to set email alerts
|

GLUT5 is a determinant of dietary fructose-mediated exacerbation of experimental colitis

Abstract: The western diet has been suggested to contribute to the rising incidence of Inflammatory Bowel Diseases. This has led to the hypothesis that fructose, a component of the western diet, could play a role in the pathogenesis of Inflammatory Bowel Diseases. A high fructose diet is known to exacerbate experimental colitis. This study tested whether the expression of GLUT5, the fructose transporter, is a determinant of the severity of experimental colitis during elevated fructose consumption and whether ileal infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Other applications include exploring the thanatomicrobiome, in determining the time elapsed since microbial death [ 56 ]. Further applications include tracking the microbiome before and after exposure to diseases like SARS COV2 [ 57 ], and determining changes in the microibial composition following dietary alterations [ 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other applications include exploring the thanatomicrobiome, in determining the time elapsed since microbial death [ 56 ]. Further applications include tracking the microbiome before and after exposure to diseases like SARS COV2 [ 57 ], and determining changes in the microibial composition following dietary alterations [ 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The western diet has been suggested to contribute to the rising incidence of inflammatory bowel diseases. A recent study reported that the interaction between fructose and its transporter, GLUT5, could shape the colonic microbiota and then impact the severity of CD [ 65 ]. Another studies showed that serum exosomes could circulate into the intestinal mucosa, regulating macrophage activation and epithelial barrier function to aggravate colitis [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons is that high fructose diet feeding can reduce the thickness of colonic mucus and alter the composition and metabolism of the gut microbiota [110] . In a recent study, SLC2A5 +/+ and SLC2A5 –/– mice fed with a 15 Kcal% fructose diet were found to exhibit more severe DSS-induced experimental colitis [111] . This effect is associated with increased level of free fructose in the colon and changes in the fecal microbiota in SLC2A5 –/– mice, and broad-spectrum antibiotics can prevent the worsening of colitis in SLC2A5 –/– mice [111] .…”
Section: Relationship Between Glut5 and Intestinal Diseasesmentioning
confidence: 93%
“…In a recent study, SLC2A5 +/+ and SLC2A5 –/– mice fed with a 15 Kcal% fructose diet were found to exhibit more severe DSS-induced experimental colitis [111] . This effect is associated with increased level of free fructose in the colon and changes in the fecal microbiota in SLC2A5 –/– mice, and broad-spectrum antibiotics can prevent the worsening of colitis in SLC2A5 –/– mice [111] . This is consistent with the conclusion that changes in GLUT5 expression lead to changes in the gut microbiota, as mentioned earlier.…”
Section: Relationship Between Glut5 and Intestinal Diseasesmentioning
confidence: 93%